Exploring the genetic association of allergic diseases with cardiovascular diseases: a bidirectional Mendelian randomization study - Wang, Shilin; Liu, Hao; Yang, Peiwen; Wang, Zhiwen; Hu, Poyi; Ye, Ping; Xia, Jiahong; Chen, Shu (Frontiers in Immunology, 2023)
Background In observational and experimental studies, allergic diseases (AD) have been reported to be associated with some types of cardiovascular diseases (CVD), as both share common pathophysiological processes involving inflammation and metabolic disorders. However, the direction of the causal association between them remains unclear. This Mendelian randomization (MR) study aims to examine the bidirectional causality between AD and CVD. Methods We utilized publicly available genome-wide association study (GWAS) summary statistics data from European participants in the UK Biobank and the IEU Open GWAS database. Genetic variants associated with AD, asthma, and CVD were identified and used as instrumental variables to investigate the genetically causal association between them. MR analyses were performed using various analytical methods, including inverse variance weighted-fixed effects (IVW-FE), inverse variance weighted-multiplicative random effects (IVW-RE), MR-Egger, weighted median, weighted mode, and maximum likelihood. Sensitivity tests were conducted to assess the validity of the causality. Results The MR analysis with the IVW method revealed a genetically predicted association between AD and essential hypertension [odds ratio (OR)=0.9987, 95% confidence interval (CI): 0.9976-0.9998, P=0.024], as well as between asthma and atrial fibrillation (OR=1.001, 95% CI: 1.0004-1.0017, P=6.43E-05). In the reverse MR analyses, heart failure was associated with allergic diseases (OR=0.0045, 95% CI: 1.1890E-04 - 0.1695, P=0.004), while atherosclerosis (OR=8.7371E-08, 95% CI: 1.8794E-14 - 4.0617E-01, P=0.038) and aortic aneurysm and dissection (OR=1.7367E-07, 95% CI: 3.8390E-14 – 7.8567E-01, P=0.046) might be protective factors of asthma. However, after a Bonferroni correction, only the association between asthma and atrial fibrillation remained robust. Conclusion The MR study revealed that asthma is a predominant risk of atrial fibrillation in European individuals, consistent with most experimental and observational studies. Whether AD affects other CVD and the causality between them needs further investigation.